Smart Contracts and the Islamic Finance Industry - Uula, Mimma Maripatul (Journal of Islamic Economics Literatures, 2025)
This study aims to examine the development of research on the topic of “Islamic Smart Contracts” and potential research plans based on journals published on this theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data on the theme “Islamic Smart Contract” from the Scopus database, with a total of 74 journal articles. The data was then processed and analyzed using the VosViewer application to map the bibliometric development of “Islamic Smart Contract” research worldwide. The results of the study found 5 clusters with the most frequently used words being smart contract, technology, blockchain, contract, transaction, fintech, blockchain technology, and islamic finance. Then, the research path topics related to Islamic Smart Contracts are Blockchain for Islamic Finance, Fintech in the Islamic Finance Industry, Smart Contracts and Cryptocurrency in Islamic Finance, Smart Contract in Sukuk and Waqf, and Islamic Smart Contracts in Banking.